Avaliação do isolamento acústico de um edifício residencial de alto padrão: estudo de caso - Paula, Dionatan José de (2022)
Given the constant growth of urban centers, it is increasingly common to employ the action of verticalizing and/or twinning buildings. Together, noise pollution is present in large cities, increasing the level of exposure to noise, generating risks such as loss of sleep and increased pressure on users of housing units. In order to provide minimum performance criteria to be met in relation to environmental comfort, ABNT NBR 15575 came into force in 2013, which addresses items such as acoustic insulation in relation to internal and external vertical fences and horizontal fences. In this way, the present study aims to analyze the acoustic insulation in relation to air noise of a high standard residential building in the city of Guarapuava-Pr, where the internal vertical sealing system for a semi-detached wall and the horizontal sealing system were analyzed. Of two overlapping autonomous housing units. The analysis was carried out for rooms of different uses, where one was intended as a bedroom and the other as a living room. The measurements followed the normative criteria, where data were collected on the levels of sound pressure, background noise and reverberation time present in the environments. The energy averages were calculated for the single insulation number obtained through programming in R code. The analysis of the data obtained shows that the studied rooms meet the minimum criteria required by the standard for both analyzed fence systems. In carrying out the comparison with other studies present in the literature, it was found that the sealing systems presented a better overall acoustic performance.